'The iceberg beneath the sea', fraudsters and their punishment through non-criminal justice in the 'fraud justice network' in England and Wales. (June 2018) - Button, Mark; Shepherd, David; Blackbourn, Dean
Abstract: This paper illustrates the substantial role of non-criminal justice bodies in punishing persons for fraud related behaviours in England and Wales. It illustrates the substantial role of government regulators, delegated regulators, self-regulators, fraudster databases and the use of contempt of court in civil courts in dealing with fraudsters. Using data from the Ministry of Justice, the number of persons sanctioned for fraud offences are juxtaposed against data drawn from the regulatory bodies within the broader 'fraud justice network'. The paper shows that over one million individuals are sanctioned for fraud offences each year and the great majority do not trouble the criminal justice system.